2021
DOI: 10.3390/molecules26185466
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry Juice Powders: Effect of Spray-Drying Conditions on the Microencapsulation of Bioactive Components and Physicochemical Properties

Abstract: The drying of fruit juices has advantages such as easy handling of powders, reduction in volume, and preservation of the characteristics of the fruit. Thus, in this work, the effect of the spray drying conditions of strawberry juice (SJ) with maltodextrin (MX) as a carrying agent on the microencapsulation of bioactive compounds and physicochemical properties was studied. The content of phenolic compounds and antioxidant activity showed higher values at low concentrations of MX, while the effect of drying tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…However, strawberry harvest is seasonal, and the fruits are perishable, susceptible to mechanical damage, and easily spoiled. For this reason, technological operations are used to preserve the fruits [4]. Furthermore, in recent years, due to environmental pollution and greater interest in a healthy diet, there has been a growing interest in organic fruit and vegetables [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, strawberry harvest is seasonal, and the fruits are perishable, susceptible to mechanical damage, and easily spoiled. For this reason, technological operations are used to preserve the fruits [4]. Furthermore, in recent years, due to environmental pollution and greater interest in a healthy diet, there has been a growing interest in organic fruit and vegetables [5].…”
Section: Introductionmentioning
confidence: 99%
“…A similar methodology was used by Cataldo et al in their work in which strawberry juice was inoculated with Levilactobacillus brevis to study the immunomodulatory effect of gamma-aminobutyric acid on rodent cell cultures [ 9 ]. In addition to processing into juice, studies have also shown the potential of processing strawberries into dry powders [ 10 ]. A considerable number of studies, including human intervention studies and cell lines using fresh or frozen fruits, extracts, purees, etc., some of which are covered in the 2014 review by Basu et al, illustrated the great potential and, what is now evident, the great interest in using strawberries as valuable health promoters [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, spray drying is the most common method to obtain amorphous solids [67]. Similar XRD patterns were found for spray-dried microencapsulated powders of strawberry juice with maltodextrin, in which an amorphous structure was confirmed by the presence of broad undefined peaks in their XRD patterns [68].…”
Section: Microstructure Of Microencapsulated Powdersmentioning
confidence: 59%